القراءة الالکترونية واستخداماتها لدى طالبات جامعة الأزهر: دراسة ميدانية - عزة عبد الحميد خطاب (المجلة الدولية لعلوم المكتبات والمعلومات)
The term electronic reading (E-Reading) is one of the modern terms in thescience of libraries and information. This study aimed to find out the effect ofelectronic reading and its uses among female students of Al-Azhar University inCairo, by knowing the motives, tendencies, and attitudes of students towards ereading. The study also aimed to identify E-reading and its impact on theeducational process, in addition to identifying the similarities and differencesbetween the effect of e-reading and the motives for its uses and its impact on theeducational process before the Corona crisis (Covid 19), and after that for thestudents of the College of Human Studies as a model.The study relied on the field method as the most appropriate method for thisThe quality of studies, as well as personal interviews, and in order to achievethese previous goals, a questionnaire was prepared for the study sample of (908)students, and some descriptive and analytical statistical methods were used,such as frequencies and percentages, using the statistical analysis programSPSS v.25.The study reached many of the results, the most important of which are:Most of the students are aware of the meaning of e-reading, by 90.75%, alsoelectronic reading has become a tangible reality that must be dealt with,electronic reading was used as a substitute for going to libraries by 74.78%, andthe printed book was affected by the emergence of electronic texts by 83.48%.The sciences of Islamic religion and heritage books are among the most readingfields. For female students, smartphones are considered the most commonelectronic reading devices used by female students, and not using dedicatedreading devices such as Sony readers, pocketbooks, and Kindles before andafter the Corona crisis.